Links Between Oral Function and Cognitive Function in Older Adults - Astari Larasati; Lindawati S. Kusdhany; Czeresna Heriawan Soejono; Muslita Indrasari (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Currently, every country in the world is experiencing a growing older adults population, both in number and proportion. The aging process in older adults is parallel to a decline in numerous physiological functions, including oral function. Older adults who encounter decreased oral function are likely to manifest symptoms such as impaired articulation, episodes of choking during eating, and an increase in the amount of food they cannot chew. Recent research reports that decreased oral function may affect brain function and trigger the onset of cognitive decline. This article review aims to explores the connections between oral function and cognitive function in older adults. Review: Today’s view of oral health is more than the number of teeth present and whether or not oral hygiene is sufficient but also includes the ability to perform functions such as mastication, tongue and lip motor skills, salivary secretion and swallowing. Decreased oral function has led to the concept of oral frailty which characterized by a gradual decline in oral functions such as chewing, swallowing, tongue pressure, and oral motor skills. Initially proposed by Tanaka, oral frailty is now recognized not merely as a dental issue but as a potential early marker of broader systemic decline, including cognitive impairment. Conclusion: Decreased oral function could also be causative factor for the onset of cognitive decline in older adults.